Contemporary Challenges and the Future of Islamic Law: Toward Ethical and Institutional Renewal - Hammadi, Hammad Farhan; Mohamed Ahmed, Ahmed; Amansyah, Fajar; Rajafi, Ahmad; Taha Alkanan, Omer Mohamed; Jabbar, Israa Natiq (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2025)
Research Objective: This study examines internal and external challenges in the Islamic world using Islamic constitutional and criminal law perspectives. It focuses on how principles, particularly those rooted in maqāṣid al-sharīah, can be applied to address legal fragmentation, underdevelopment, Islamophobia, and marginalization. Research Method: A qualitative normative approach was used, supported by thematic and comparative analysis. It draws on primary Islamic texts, constitutions, international legal sources, and academic literature. Case studies from Indonesia and the UAE illustrate different applications of Islamic law in governance and justice. Results: The findings indicate that challenges stem primarily from structural, rather than theological, issues. Internally, these include stagnant education systems, fragmented financial structures, and inconsistent Sharia application. Externally, they involve widespread Islamophobia and limited global representation. Findings and Implications: Islamic legal norms align with democratic values such as equity, participation, and justice. Ethical tenets like maṣlaḥaḥ and shūra support pluralistic governance. Institutional reform and contextual application of Islamic law can improve both domestic legitimacy and international engagement. Conclusion: Islamic legal systems hold the flexibility and strength to meet governance needs. Realizing their potential requires structural reform and aligning jurisprudence with contemporary legal frameworks. Contribution: This study contributes to Islamic legal scholarship by presenting a model that connects classical jurisprudence with modern constitutional practice. It adds to interdisciplinary work, promoting Islamic law in global legal discourse. Limitations and Suggestions: The non-empirical nature and limited jurisdictional scope of the study constrain broader generalization. Future research should incorporate empirical approaches and explore how digital innovation can support Islamic governance reforms.